Imaginação e protagonismo na educação infantil: estreitando os vínculos entre adultos e crianças - Moreira, Tony Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research was carried out at the Graduate Program in Education of the Faculty of Science and Technology, UNESP - Presidente Prudente, linked to the research line called Formative Practices and Processes in Education. The study was conducted in two early childhood education establishments located in two municipalities in the state of São Paulo (Presidente Prudente and Álvares Machado). It has emerged from an action-research on the cultures of childhood held in the same educational institutions, in which was found the lack of appreciation and understanding of children's imaginative language by teachers and other professionals. The precursor study aroused the interest of the teachers in broadening their knowledge of the child's imagination and in qualifying their practices in the same area of study. To meet these needs, the theoretical framework of this research was composed mainly by the Sociology of Childhood and studies of Paul L. Harris, where both theories have innovative assumptions, by which the child is seen as an active social subject, the childhood consists of a social category of generational types and imagination represents a fundamental human language that has a special dimension in childhood, even though it is developed over the period of a lifetime. The research aimed to promote a greater understanding of children's imaginative language by the subjects from both of the investigated institutions. Furthermore, a joint production of knowledge about child imaginative language as a support to strengthen the interests and needs of children educational practices was also targeted . Specific objectives : expanding the experiences geared to the child's imagination through the development of play and fantasy games with the participant children, and surveying procedures to behold the child imaginative language in pedagogical approaches of the participating teachers...

Esta investigação foi desenvolvida junto ao Programa de Pós Graduação em Educação da Faculdade de Ciências e Tecnologia, UNESP – Campus de Presidente Prudente, vinculada a Linha de Pesquisa denominada Práticas e Processos formativos em Educação. O estudo foi realizado em duas instituições de Educação Infantil de dois municípios do estado de São Paulo (Presidente Prudente e Alvares Machado), surgiu a partir de uma pesquisa-ação sobre as culturas da infância realizada nas mesmas instituições educacionais, pela qual foi constatada a falta de valorização e compreensão da linguagem imaginativa infantil pelas professoras e outros profissionais dessas instituições. O estudo percursor despertou o interesse das professoras em ampliar os seus conhecimentos sobre o imaginário infantil e qualificar suas práticas. Para corresponder a essas necessidades o referencial teórico desta pesquisa foi composto principalmente pela Sociologia da Infância e os estudos de Paul L. Harris, ambas as teorias apresentam pressupostos inovadores, pelos quais a criança é entendida como um sujeito social ativo, a infância consiste em uma categoria social do tipo geracional e a imaginação representa uma linguagem humana fundamental que tem uma dimensão especial na infância, mas é desenvolvida a longo de toda a vida. A investigação teve como objetivo principal a promoção de uma maior compreensão da linguagem imaginativa das crianças por parte dos sujeitos das duas instituições investigadas e uma produção conjunta de conhecimentos sobre a linguagem imaginativa infantil como subsídio para práticas educativas mais próximas aos interesses e necessidades das crianças...
Keywords: Educação; Imaginação nas crianças; Infância; Educação de crianças; Education